ROLE OF HERBS IN INTRACANAL MEDICAMENTS - PRATISHTA JAIN; MANISH RANJAN (International Journal of Pharma and Bio Sciences, 2014)
The major objectives of an endodontic treatment are to remove the diseased tissue, eliminate bacteria from the root canal system and prevent its recontamination. Intracanal medicaments are used in a root canal treatment to eliminate any remaining viable bacteria in the root canals after instrumentation, to reduce the inflammation of periapical tissues and to prevent reinfection of the root canal system. For this purpose, a wide variety of synthetic antimicrobial agents are available but due to their adverse effects on the host like hyper sensitivity, immune suppression and allergic reactions, there’s a need to find natural plant based alternatives for these conventional drugs. Herbal alternatives are affordable, effective and non toxic. Thus, this review aims at providing a comprehensive overview of the various herbal agents that can be used as effective intracanal medicaments.